KEKERASAN VERBAL DALAM FILM KARTUN KIKO(VERBAL VIOLENCE IN THE KIKO CARTOON FILM) - Ika Anggraeni Ratna Sari (Universitas Lambung Mangkurat, 2020)
Verbal Violence in the Kiko Cartoon Film. This research aims to describe theverbal violence in the forms of the directive, and expressive speech acts in the Kikocartoon. This was qualititative research. The data were the words or sentencesused in the Kiko cartoon. The data source of research was the cartoon film of Kiko.Data were collected using the note-taking technique. The research instrument usedwere laptop and data cards. Laptop and data cards are used as a video player andas a tool to listen and understand the utterances in the Kiko cartoon. Furthermore,the data collected were analyzed based on verbal violence in the forms of thedirective, and expressive speech acts. The additional instrument was the data cardsby which the researcher collected data on the types off speech acts and groupedthem according to the directive and expressive speech acts and grouped themaccording to the directive and expressive speech acts. The results of the researchindicated that 117 speech acts including 33 types of rebuked violence, 55 types ofharassment, two types of accusations, 20 types of coercion, and seven types ofintimidation. b) 56 directive speech acts consisting of 29 commandment speechacts, 2 threat, seven rejection seepch acts, 13 opposing speech acts, five denialspeech acts. c) 61 expressive speech acts consisting of 11 speech acts forexpressing displeasure, 17 speech acts for criticizing, 15 speech acts for swearing,15 speech acts for insulting, and there speech acts for exspressing satire.Key words:verbal violence, Kiko cartoon film